Functional connectivity changes within specific networks parallel the clinical evolution of multiple sclerosis - Basile, B; Castelli, M; Monteleone, F; Nocentini, U; Caltagirone, C; Centonze, D; Cercignani, M; Bozzali, M (Multiple sclerosis, 2014)
Background: In multiple sclerosis (MS), the location of focal lesions does not always correlate with clinical symptoms, suggesting disconnection as a major pathophysiological mechanism. Resting-state (RS) functional magnetic resonance imaging (fMRI) is believed to reflect brain functional connectivity (FC) within specific neuronal networks. Objective: RS-fMRI was used to investigate changes in FC within two critical networks for the understanding of MS disabilities, namely, the sensory-motor network (SMN) and the default-mode network (DMN), respectively, implicated in sensory-motor and cognitive functions. Methods: Thirty-four relapsing–remitting (RR), 14 secondary progressive (SP) MS patients and 25 healthy controls underwent MRI at 3T, including conventional images, T1-weighted volumes, and RS-fMRI sequences. Independent component analysis (ICA) was employed to extract maps of the relevant RS networks for every participant. Group analyses were performed to assess changes in FC within the SMN and DMN in the two MS phenotypes. Results: Increased FC was found in both networks of MS patients. Interestingly, specific changes in either direction were observed also between RR and SP MS groups. Conclusions: FC changes seem to parallel patients’ clinical state and capability of compensating for the severity of clinical/cognitive disabilities.